A bibliometric analysis of chemotherapy and pain in pediatric patients over the last decade - Huang, Hua; Cai, Guowei; Xiang, Hongchun (Frontiers in Pediatrics, 2023)
Background Chemotherapy is an important treatment for children with cancer, and chemotherapy-induced pain is an important role in affecting patients' quality of life. In our study, bibliometric analysis was used to identify current research hotspots and future research trends of chemotherapy and pain in children over the last decade. Our findings can provide a reference for the research in the field of chemotherapy and pain in children. Method Publications of chemotherapy and pain in children were collected from the Web of Science Core Collection database. CiteSpace was used to analyze publication characteristics from 2013 to 2022. Results We identified 1,130 eligible publications in the field of chemotherapy and pain in children, with an increasing trend of publications over the last decade. In the field of chemotherapy and pain in children, the United States had the most publication with 346, followed by China with 135. The author with the most published papers was Pamela S Hinds (n = 8) from the United States. The journals that published the most papers were the Journal of pediatric hematology oncology (n = 44) and Medicine (n = 44). The Journal of Clinical Oncology was cited the most frequency (n = 422). St. Jude Children's Research Hospital had the most publication (n = 23). The specific keywords related to the field of chemotherapy and pain in children were “children”, “chemotherapy”, “management”, “childhood cancer”, “randomized controlled trial” and “efficacy”. Emerging research focuses predominantly on symptomatic and supportive interventions for chemotherapy and pain in children. Conclusion Attention to chemotherapy and pain in children with cancer was insufficient. This bibliometric analysis showed the upward trend of chemotherapy and pain in children over the last decade. More studies are needed to improve the quality of life in children with chemotherapy-induced pain. This study may provide useful information to guide future research on chemotherapy and pain in children.